2003
DOI: 10.1063/1.1575192
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-Zn+/Zn2+ and their hydrates: On the number of water molecules necessary to stabilize the switterionic glycine-Zn+/Zn2+ over the nonzwitterionic ones

Abstract: Several interaction modes of glycine with one Zn ϩ or Zn 2ϩ and further with one and even two H 2 O molecules in the gas phase are studied at the hybrid three-parameter B3LYP and Hartree-Fock level, respectively. On the basis of these optimized geometries, single point calculations are performed using different theoretical methods and larger basis sets. The calculated results imply that the most stable glycine-Zn ϩ isomer is a five-membered ring with Zn ϩ bound to both amino nitrogen and carbonyl oxygen ͑NO͒ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(107 citation statements)
references
References 34 publications
5
101
1
Order By: Relevance
“…For Gly⅐Ni ϩ and Gly⅐Cu ϩ , the nonzwitterion forms are ϳ14 and 10 kcal/mol more stable, respectively [31,32]. Attachment of divalent alkaline earth metal ions (except Be 2ϩ ) [33], Cu 2ϩ [32] and Zn 2ϩ [29] can make the zwitterion or salt-bridge form of glycine more stable by 5-12 kcal/mol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For Gly⅐Ni ϩ and Gly⅐Cu ϩ , the nonzwitterion forms are ϳ14 and 10 kcal/mol more stable, respectively [31,32]. Attachment of divalent alkaline earth metal ions (except Be 2ϩ ) [33], Cu 2ϩ [32] and Zn 2ϩ [29] can make the zwitterion or salt-bridge form of glycine more stable by 5-12 kcal/mol.…”
mentioning
confidence: 99%
“…The zwitterion form can be made more stable by attaching a metal ion or an electron to it. Calculations indicate that an attached alkali metal cation [23][24][25][26][27], silver (I) ion [28], or zinc (I) ion [29] can lower the relative energy of the zwitterion or salt-bridge form of glycine to only 1-4 kcal/mol higher in energy than the nonzwitterion or charge-solvated form of these ions. Experimental evidence indicates that only the chargesolvated form exists in the gas phase [26,30].…”
mentioning
confidence: 99%
“…A number of studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] have been done to investigate the role of monovalent and divalent metal cations and also with explicit addition of water molecules on the structural stability of Ala and ZAla in both, gas phase as well as aqueous medium. In our recent study [43], the theoretically calculated Raman spectra of hydrogen bonded complexes of ZGly with 1-5 water molecules were compared to the experimentally recorded Raman spectra of Gly in aqueous medium and we observed that the calculated Raman spectra of ZGly with five water molecules were found to be in good agreement with the experimentally recorded Raman spectra in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible mechanisms of free radical induction by ZnO nanoparticles was proposed by Ai and co-workers (2003) which is that sequential oxidation-reduction reaction may occur at ZnO particle surface to produce reactive species such as H 2 O 2 and hydroxyl radical (Ai, 2003). Some limitations of utilising this probe exist, even though it is often assumed that H 2 O 2 (in presence of cellular peroxidases and similar catalysts) and hydroxyl radicals (˙OH) can oxidise DCFH (Ai, 2003).…”
Section: +mentioning
confidence: 99%